A case of reccuring giant condyloma of vulva in infant without sexual abuse successfully treated with electrocoagulation in Benin - ADEGBIDI, HUGUES DANIEL GBADEBO (My University, 2017)
We report here a case of giant vulval condyloma in a two-year-old infant infected by her "baby sitter" without sexual abuse. Treated by surgical excision coupled with electrocoagulation, it was noted a rapid recurrence two weeks after treatment requiring a second electrocoagulation session. More than a year later, no lesion was noted, thus demonstrating therapeutic success. The unavailability of imiquimod in our context requires a systematic use of invasive treatment regardless of the age of the patient.
Keywords: Giant condyloma; infant; electrocoagulation; Benin; West Africa